Effect and Safety of Mycophenolate Mofetil in Idiopathic Pulmonary Fibrosis - Argyris Tzouvelekis; Evangelos Bouros; Anastasia Oikonomou; Paschalis Ntolios; George Zacharis; George Kolios; Demosthenes Bouros (Pulmonary Medicine)
Background. Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic interstitial lung disease with ineffective treatment. Mycophenolate mofetil (MMF) is an immunomodulatory agent which inhibits lymphocyte proliferation. Objective. We sought to determine the safety and efficacy profile of MMF in IPF patients. Methods. We retrospectively identified ten patients, who met the ATS/ERS 2000 criteria for IPF and received MMF 2 gr/day for 12 months. All of them had routine laboratory, pulmonary function and radiological (high resolution computed tomography-HRCT) data available and were enrolled in the study. Forced vital capacity (FVC), total lung capacity (TLC), diffusion capacity of the lung for carbon monoxide (DLCO), 6-minute walking distance (6MWD), HRCT scans and routine laboratory data at treatment onset were compared with respective values 12 months after treatment onset. Results. There were no significant alterations in FVC, TLC, DLCO and 6MWD pre- and 6 and 12 months post-treatment. HRCT evaluation showed deterioration of the total extent of disease (P=0.002) and extent of ground-glass opacity (P=0.02). No cases of clinically significant infection, leucopenia, or elevated liver enzymes were recorded. Conclusions. MMF is a safe therapeutic modality which failed to show a beneficial effect both in functional and radiological parameters in a small cohort of IPF patients.